2019
DOI: 10.1080/14606925.2019.1594977
|View full text |Cite
|
Sign up to set email alerts
|

Considering Haptic Feedback Systems for A Livable Space Suit

Abstract: The paper explores protective equipment for work in extreme environments manifested in a proposal for a haptic feedback system for astronauts. It follows the thesis that the safety of astronauts wearing Extra-Vehicular Activity (EVA) suits, whether in space or on planetary surfaces, is connected to their ability to interact with their environments, their equipment and suits, and their coworkers. The project emphasises the use of new technologies to enhance the quality of said interactions. Focusing on manned e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For example, it could be useful for recognizing alerts (Salzer, Oron-Gilad, Ronen and Parmet, 2011) such as during flight or egress. Vibrotactors could be used as a sensory augmentation device, enhancing performance of manual control tasks (Clément et al, 2018) such as during extravehicular activity (Bakke and Fairburn, 2019). After landing on the surface of a planet or the Moon or returning to Earth, vibrotactile feedback could likely help with postural instability (Sienko et al, 2013;Wall, 2010), and later on, with navigation while exploring the surface (Erp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it could be useful for recognizing alerts (Salzer, Oron-Gilad, Ronen and Parmet, 2011) such as during flight or egress. Vibrotactors could be used as a sensory augmentation device, enhancing performance of manual control tasks (Clément et al, 2018) such as during extravehicular activity (Bakke and Fairburn, 2019). After landing on the surface of a planet or the Moon or returning to Earth, vibrotactile feedback could likely help with postural instability (Sienko et al, 2013;Wall, 2010), and later on, with navigation while exploring the surface (Erp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…An investigation on multimodal displays found that the use of vibrotactile feedback in reduced visibility environments for obstacle cues and avoidance minimized heads-down time, created a more conservative gait, and optimized foot placement 91 . Another team of researchers proposed the concept of haptic feedback (or a periphery cap system) as a means of relaying information to the crew member 92 . The cap would have a haptic language of its own and would assist in the filtration of sensory input through the layers of the spacesuit 92 .…”
Section: Eva Operational Risksmentioning
confidence: 99%
“…Another team of researchers proposed the concept of haptic feedback (or a periphery cap system) as a means of relaying information to the crew member 92 . The cap would have a haptic language of its own and would assist in the filtration of sensory input through the layers of the spacesuit 92 . In addition, the haptic cap may reduce the cognitive load for the user since information normally transferred through touch will now have a channel to the user inside the suit 92 .…”
Section: Eva Operational Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Haptic technology is a type of assistive technology that uses a sense of touch to convey information to the brain and spinal cord via the use of forces, vibrations, or movements [1]. Due to their ability to improve cognitive load deficiencies [2], haptic systems are used in various industries, including consumer products and medicine [3]. Indeed, it has been shown that the skin's touch receptors may transmit a wide range of information, such as instructions, words, and more [4].…”
Section: Introductionmentioning
confidence: 99%